Intranasally delivered colostrum-derived small extracellular vesicles mitigate acute neuroinflammation in periventricular leukomalacia - Ture, Beyza; Erdogan, Funda; Armagan, Coskun; Tastan, Bora; Gonul, Ceren Perihan; Guducu, Yusuf; Akyildiz, Can; Duman, Nuray; Genc, Sermin; Ozkan, Hasan (Brain research, 2026)
[Display omitted] •This article demonstrates that intranasally delivered colostrum-derived sEVs can reach the neonatal brain.•The results suggest that colostrum sEVs mitigate PVL-like injury and show promise for neonatal brain injury.•Intranasal sEV delivery has potential as a non-invasive translational strategy, for neonatal white-matter injury. Periventricular leukomalacia (PVL) is a predominant white matter injury in preterm infants, leading to lifelong neurodevelopmental disability, and yet disease-modifying therapies are lacking. Breast milk, especially colostrum, contains bioactive components with potential neuroprotective properties, among which extracellular vesicles (EVs) have recently attracted increasing attention. This study aimed to evaluate the neurorestorative efficacy of intranasally administered colostrum-derived small EVs (sEVs) in a lipopolysaccharide (LPS)-induced PVL model. sEVs were isolated from Sprague-Dawley rats’ colostrum and characterized by Nanoparticle Tracking Analysis (NTA) and Western blot (WB). To assess brain delivery following intranasal administration, sEVs were labeled with PKH67. Neonatal pups were randomly assigned to three groups: control, systemic LPS, and LPS + sEVs. A PVL-like model was induced (LPS) injection at postnatal day 5 (P5), and intranasal sEVs were administered thereafter. Brains were analyzed at P11. Labeled sEVs were detectable in the hippocampus and corpus callosum (CC) within 3 h of intranasal delivery. LPS increased microglial and astroglial markers (Iba1, GFAP) and reduced neuronal/Oligodendroglial markers (NeuN, Olig2), whereas sEVs treatment partially normalized these indices in both regions. Colostrum-derived sEVs reach the neonatal brain via the intranasal route and mitigate LPS-induced neuroinflammatory changes. These findings support intranasal sEVs as a non-invasive candidate approach for neonatal white-matter injury. To our knowledge, this is the first demonstration that intranasally delivered colostrum-derived sEVs can penetrate the neonatal brain and ameliorate histological indices of PVL-like injury, suggesting that this approach could be a novel and promising treatment strategy for neonatal brain injury.